MANAJEMEN DIKLAT DALAM UPAYA OPTIMALISASI KINERJA PEGAWAI PUBLIK - Rosidah Rosidah (Jurnal Manajemen Kepegawaian, 2008)
Training is a form of employee development toward achieving the vision and mission of an organization. The process toward achieving vision and mission is inseparable from various challenges such as: technological development, politic, social, and the demand for good quality service. In order to get the right balance as a result of those challenges, the existence of qualified human resoure that meet the required qualification needs to be taken into account in order to obtain effective work as demanded by either internal and external stakeholder. One of the efforts that can done is by improving the training management. Trainig will be more effective when it is capable of transforming one’s attitudes to meet the organizational goals. In accordance to that, there are some stages needed to be done : 1) planning stage which involves needs analysis, setting objectives for the training management development, the material/curriculum, time/duration of training, trainer and method of training, 2) the training which involves setting the committee either in organizing committee, those belong to the training organization and sterring committee, those immediately in charge of the training, 3) evaluation stage can be conducted through the following alternatives: post test, pretest/post test, or multiple pretest/multiplepost test, or post training action plan. Key word: training, human resource